Analisis Problem Gap Pencatatan Murabahah pada Lembaga Keuangan Syariah dan Implikasinya terhadap Kepercayaan Nasabah - Eka Allafta Firman; Muh. Akwan; Masyhuri (Journal of Islamic Economic Studies, 2025)
This research is motivated by the incompatibility between the sharia accounting standards of PSAK 102 and the practice of recording murabahah transactions in Islamic financial institutions. The purpose of this study was to identify these practice gaps and analyze their impact on customer confidence levels. This study uses a qualitative descriptive approach with a literature study method that examines secondary sources, such as scientific journals, accounting standards, and regulatory documents. The results of the study show that many institutions have not implemented PSAK 102 consistently, especially related to the recognition of profit margins and the presentation of selling prices. In addition, low customer participation in understanding murabahah contracts leads to information asymmetry and decreased transparency. The implications of this ambiguity negatively impact customer perception, weaken trust, and threaten the credibility and sustainability of Islamic financial institutions. These findings show that the problems faced are not only technical, but also include ethical and institutional dimensions. Therefore, a commitment to standard-compliant reporting, higher transparency, and active involvement of customers in the transaction process is needed to uphold Islamic financial principles.